Experimental datasets from mechanical testing and characterization of composites filled with PVCs wasteMendeley Data - Ariyana Dwiputra Nugraha; Edi Purnomo; Fachri Rozi Afandi; Heru Wijayanto; Nugroho Karya Yudha; Eko Supriyanto; Alvin Dio Nugroho; Muhammad Akhsin Muflikhun (Data in Brief, 2025)
This paper reports an investigation into composites containing photovoltaic (PVC) waste as a filler, offering a detailed set of data based on mechanical testing, material characterization, and simulation. The fabrication and testing of specimens followed established standards: ASTM D638 for tensile testing, ASTM D790 for flexural testing, ASTM D2240 for hardness, and ASTM D695 for compression tests. To ensure accuracy, the dimensions of the specimens were measured at three distinct points. The tensile tests were simulated using Abaqus 2023. The distribution of PVC waste as a composite filler can be observed using SEM/EDS, and FTIR analysis is used to identify the compounds present in the specimen. The data generated above provides information that the best ultimate tensile strength was obtained from the 4 % PVCs variation at 51.43 MPa, followed by a flexural strength of 45.54 MPa and a compressive strength of 35.38 MPa. The results of the SEM/EDS analysis indicate that the PVCs are primarily composed of carbon and silica. Additionally, a simulation utilising the Abaqus application was performed, revealing a discrepancy of <2 %. This data can be utilised by professionals in the field for further studies or to develop composites that incorporate PVC waste as a filler.